2020
DOI: 10.12965/jer.2040076.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined aquatic and cognitive training on quality of life, fall self-efficacy, and motor performance in aged with varying cognitive status: a proof-of-concept study

Abstract: With the increasing number of aged individuals, research pertaining to their cognitive functions and physical-motor has become exponentially imperative. The purpose of the study was to investigate the effect combined aquatic and cognitive training on quality of life (QoL), fall self-efficacy and motor performance (static and dynamic balance) in aged with varying cognitive status levels. Thirty participants were assigned to a high cognitive status group (n= 10), low cognitive status group (n= 10), or noninterve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Matson et al (2019) report that seniors undergoing health reeducation (including physical activity) improved their self-efficacy, as well as their perception of quality of life. In the study by Nahand et al (2020), which undertook an intervention with exercises and cognitive training with elderly people, they found that quality of life can be improved in elderly people with low cognitive test scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Matson et al (2019) report that seniors undergoing health reeducation (including physical activity) improved their self-efficacy, as well as their perception of quality of life. In the study by Nahand et al (2020), which undertook an intervention with exercises and cognitive training with elderly people, they found that quality of life can be improved in elderly people with low cognitive test scores.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity can also contribute to good perception of quality of life. This occurs due to the biopsychosocial aspect of this practice (Gomes et al, 2020), because it promotes increased mobility (Skwiot & Juskiewicz-Swaczyna, 2017), cognitive improvements (Nahand et al, 2020) and increased social interaction (Matson et al, 2019), especially in collective practices, resulting in their well-being and positive health conditions (Frandin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation